GLUT4 JARINGAN ADIPOSA FUNGSI DAN DISFUNGI - Kaunang, Henry C. P.; Wangko, Sunny (UNIVERSITAS SAM RATULANGI, 2010)
Abstract: Following the discovery of insulin nearly a century ago, it has become easier to comprehend the mechanism of this peptide hormone. Insulin activates the phosphorylation of tyrosine kinase and consequently triggers the intracellular signals that regulate most of the processes within the cells of our body. In order to maintain the glucose homeostasis, insulin reduces glucose production in the liver and increases glucose uptake into muscles and adipose tissues by escalating the glucose transporter 4 (GLUT4) translocation from within the cells to the outer part of the membranes. Many efforts have been put forth out of the curiosity of scientists to provide answers, but further exploration of insulin receptor signaling pathways and junctures in trafficking has made it clear that many questions are left unanswered. Interestingly, these questions are being more focused on; hence, the functional molecules, in particular those that were required for insulin signaling cascades and junctures of GLUT4 vesicle trafficking have become the interest for further research. The degenerative diseases with broad complications due to the impaired of glucose homeostasis preserved by insulin have become the main target in developing a therapy or even prevention. Many joint efforts of scientists using numerous research methods offer great expectations for better comprehension of regulating the GLUT4 vesicle trafficking. Keywords: insulin stimulation, adipose tissue, GLUT4 trafficking Abstrak: Dengan ditemukannya insulin hampir seabad lalu, semakin banyak yang diketahui tentang mekanisme kerja hormon peptida ini. Insulin memfosforilasi tirosin kinase sekaligus juga mengaktifkannya sehingga memicu kaskade sinyal intrasel yang meregulasi sebagian besar proses di dalam sel. Untuk mempertahankan homeostasis glukosa, insulin menekan produksi glukosa di hepar dan meningkatkan ambilan glukosa pada jaringan otot dan adiposa dengan meningkatkan translokasi transporter glukosa 4 (GLUT4) menuju permukaan membran plasma. Telah banyak usaha yang dilakukan untuk menjawab keingin-tahuan para ilmuwan, namun semakin menggali ke dalam kompleksitas molekular lintasan sinyal reseptor insulin dan tahapan-tahapan proses trafficking, semakin banyak pertanyaan yang muncul ke permukaan. Hal ini menarik untuk dikembangkan karena spesifitas molekul fungsional yang dibutuhkan untuk kaskade sinyal insulin dan tahapan trafficking vesikel GLUT4 dapat menjadi titik tangkap untuk penelitian. Penyakit degeneratif dengan komplikasi yang luas akibat terganggunya homeostasis glukosa oleh insulin menjadi sasaran utama dalam pengembangan terapi penanganan atau bahkan pencegahan. Upaya para peneliti dengan penggunaan beragam metode penelitian sangat diharapkan mampu memberikan secercah cahaya dalam memahami regulasi insulin dalam trafficking vesikel GLUT4 Kata kunci: stimulasi insulin, jaringan adiposa, trafficking GLUT4